Intra-aortic balloon pump (ΙΑΒΡ): from the old trends and studies to the current “extended” indications of its use - Parissis Haralabos; Soo Alan; Al-Alao Bassel (Journal of Cardiothoracic Surgery, 2012)
Abstract This report outlines the well defined indications of using IABP and also favours extending the indications of IABP use, to include not only “therapeutically” the aging unstable patients but also “prophylactically” patients with low EF or high Euroscore.